1971
DOI: 10.1146/annurev.pp.22.060171.002243
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity

Abstract: Man's dependence upon food resources from cultivated lands had its genesis some 10,000 years ago, and the resulting technology of crop hus bandry has been the principal factor permitting large increases in human population. The potential for food production in conventional agriculture and in alternative systems is undergoing intensive re-examination now be cause of current rapid population growth and attendant pressures for conver sion of highly productive, cultivated lands to other uses. The develop ment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
3

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 128 publications
5
52
0
3
Order By: Relevance
“…When such conditions occur, it seems unlikely that sucrose will accumulate and result in a feedback inhibition of photosynthesis (16). Such an inhibition occurring in agricultural crops in the field is likewise doubtful since crowded plants have much more sink than source capacity (15). Unfortunately in this study, translocation was only a small percentage of net photosynthesis (20-25%) probably a result of the relatively immature stage of the source leaves (23).…”
Section: Discussionmentioning
confidence: 58%
“…When such conditions occur, it seems unlikely that sucrose will accumulate and result in a feedback inhibition of photosynthesis (16). Such an inhibition occurring in agricultural crops in the field is likewise doubtful since crowded plants have much more sink than source capacity (15). Unfortunately in this study, translocation was only a small percentage of net photosynthesis (20-25%) probably a result of the relatively immature stage of the source leaves (23).…”
Section: Discussionmentioning
confidence: 58%
“…Several authors have reported an increase in root/ shoot ratios of plants growing under water stress (Peters andRunkles 1967, Black 1968). According to Loomis et al (1971) the water stress slows shoot growth more and sooner than it does root growth. The root/shoot behaviour of Poa and Lolium did not conform to the above findings (e.g., Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed in part to the greater functional importance of aboveground as opposed to below-ground competition, as identified in many systems (e.g. Donald, 1958;Loomis et al, 1967Loomis et al, , 1971. Alternatively, this outcome may also in part be attributed to the widely observed general allometric relationships linking aboveground and below-ground performance and productivity.…”
Section: Introductionmentioning
confidence: 97%